Evaluasi Pengelolaan Obat dan Bahan Medis Habis Pakai di Puskesmas Kota Kupang serta Strategi Pengembangannya - Novi Winda Lutsina; Arman Rifat Lette (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
The management of drugs and disposable medical supplies in healthcare units greatly affects the quality of healthcare services. However, the management is still not carried out optimally because it is not up to the standard. The Hanlon method is a basic priority rating system (Brief Priority Rating Scale, BPRS) which is used to compare health problems with relative and objective to identify factors that must be considered in determining a priority. This study aimed to describe and measure the efficiency of drugs and disposable medical supplies management in Healthcare Centers in Kupang City by using efficiency indicators and to develop the strategy using the Hanlon method. The design of this research is a descriptive quantitative-qualitative combination using retrospective and concurrent data. The sampling technique used was a total sampling of 11 Healthcare Centers in Kupang City, while the object of the study was the management of drugs and disposable medical supplies which were assessed using efficiency indicators. The results of research on the management of medicines and consumable medical materials at 11 Healthcare Centers in Kupang City have not been carried out efficiently because not all indicator values reached the standard, namely the suitability of drug items with DOEN and FORNAS, conformity of items received, the accuracy of planning, items expired or damaged, items that were not prescribed for 3 months, the level of availability of the drug, the percentage of drugs with generic names, use of antibiotics in patients with non-specific diarrhea and the average item per prescription sheet. Therefore it can be concluded that the management of drugs and disposable medical supplies in 11 Healthcare Centers in Kupang City using indicators at the selection, procurement, distribution, and use stages are not yet according to standards and the proposed improvements are proposed as a management development strategy, namely optimizing planning according to the needs of the health center, monitoring stock. and expiration date and conduct regular learning and growth of all human resources.